Solid lubricants and surfaces - Braithwaite, E. R. (Eric Reeves) (Pergamon Press, 1964)
Solid Lubricants and Surfaces deals with the theory and use of solid lubricants, particularly in colloidal form. Portions of this book are devoted to graphite and molybdenum disulfides, which are widely used solid lubricants in colloidal form. An extensive literature on the laboratory examination of hundreds of solids as potential lubricants is also provided in this text. Other topics discussed include the metals and solid lubricants; techniques for examining surfaces; other solid lubricants; metal shaping; and industrial uses of solid-lubricant dispersions. This publication is beneficial to e.